ANALISIS PENERAPAN PRODUKSI BERSIH PADA INDUSTRI TEMPE - Tauny Akbari; Leni Sumarni (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Tempe is one of Indonesia's special foods made from soybeans. This study aims to identify and analyze application of cleaner production to the tempe industry. Analysis of the application of cleaner production is done by the quick scanning method at each stage of the production process and then tested for its technical and economic feasibility (PBP). The analysis results of the application of cleaner production in the tempe industry are tool modification, fuel substitution, use of personal protective equipment, reuse, recycle and reduce. Based on the results of technical and economic feasibility tests, the alternative application of cleaner production in the form of solid waste utilization of soybean husks as animal feed is the first priority scale to be applied to the tempe industry